Análise reflexiva do ensino de Libras como primeira e segunda língua - Anjos, Orilande Nogueira dos (Brasil, 2022)
Does this Course Completion Work (TCC) present in a succinct way the clinical and socioanthropological aspects of the understanding of deafness, as a disease or an integral subject of the minority society? Belonging to its own culture that determines the deaf identity, the factors that identify who are the members linked to the deaf community. Just like Gesser (2010, 2012), Quadros(1997), Wilcox(1997), Leite(2004), Felipe(2007), Cláudio (2017), Brown (1994), Lizzio(2011) are acquisition/teaching researchers of language, regardless of the oral or visual modality, they all have facts in common in their process. A bibliographic study was developed and compared with the empirical experiences of this author in the Libras course, the comparative basis and the communicative methodology to carry out an analysis with the following questions: Does the hearing subject have the same proficiency in Libras as L2 in the acquisition process/ learning? Do hearing learners with mastery in L1 (Portuguese), do they have the same L2 learning difficulties as the deaf subject? How long can the adult subject be able to have fluency in Libras as L2? Having as objectives to present the communicative teaching method of the adult hearing subject in the teaching and learning process of Libras as L2; mention the process of language acquisition of Libras as L2, of the hearing student in Manaus and report empirical experiences in the process of acquisition of the language of the hearing student.